THE EFFECTS OF LYSOPHOSPHATIDYLINOSITOL AND 17?-ESTRADIOL ON EXPRESSION OF GPR55 AND ACTIVATED PROLIFERATION SIGNALLING PATHWAY IN OVARIAN CANCER CELL LINE SKOV-3 - Yelliantty
Serum Lysophosphatidylinositol (LPI) level was found to be higher in ovarian cancer patients than healthy women. It shows a potential role of LPI in development of ovarian cancer. The role of LPI in the development of ovarian cancer has not been clearly established. G-protein coupled receptors 55 (GPR55) is a receptor that can bind to the LPI. It was found that the signaling pathway of GPR55 induced by LPI involved ERK1/2 that lead to cell proliferation. Healthy ovary or ovarian cancer can produce and be a major source 17?-estradiol. Latest study showed that 17?-estradiol induced GPR55 gene expression in ovarian cancer cell line SKOV-3. This raised a presumption of relationship between the LPI, 17?-estradiol and GPR55 in the development of ovarian cancer. Therefore it is necessary to study the effect of LPI and 17?-estradiol on the expression of GPR55, the signalling pathways activated by GPR55, and its involvement in proliferation of ovarian cancer. The aim of this study was to determine the effect of LPI and 17?-estradiol on expression of GPR55, ERK1/2, pERK1/2 and on proliferation of ovarian cancer cell line. Ovarian cell line SKOV-3 was used in this experiment. SKOV-3 was treated with LPI and 17?-estradiol. GPR55, ERK1/2, pERK1/2 and cell proliferation marker PCNA were assessed in SKOV-3 treated with LPI and 17?-estradiol. Protein expression analysis was performed using Western blotting analysis and ?-actin was used as an internal control. The results of Western blotting was analyzed using SCION-IMAGE software. The results showed the highest expression of GPR55 was found in the SKOV-3 cells treated by 17?-estradiol. However, expression of GPR55 in the untreated SKOV-3 cells was higher than cells treated with LPI. It showed that 17?-estradiol could induce an increase in GPR55 expression, whereas LPI gave the opposite effect. LPI suppressed expression of GPR55 in SKOV-3. ERK1/2 and pERK1/2 was found highest in cells treated with 17?-estradiol and LPI, LPI, 17?-estradiol, and the lowest was in untreated cells. In addition, the data also showed a synergistic effect between LPI and 17?-estradiol in activating ERK1/2 in SKOV-3 cells. The results also indicated a difference in proliferation marker PCNA in each treatment group. Highest expression of PCNA was seen in cells treated by LPI and 17?-estradiol. PCNA expression in cells treated by LPI was lower than 17?-estradiol group, whereas SKOV-3 cells in control group expressed lowest PCNA expression than other cell groups. These results showed that LPI and 17?-estradiol could induce proliferation of SKOV-3 ovarian cancer cells. GPR55 in the LPI group of cells was lower than controls. This indicated that LPI does not induce the expression of GPR55. Additionally, effect of 17?-estradiol on proliferation is stronger than LPI. Decreased existence of GPR55 in the treatment group LPI may be caused by desensitization mechanisms, which GPR55 could be degraded after binding to LPI. Signalling pathway through which the LPI-GPR55 in cancer cell lines SKOV-3 might involve in ERK1/2 activation, which lead to proliferation. Based on the results, it can be concluded that the LPI did not affect the expression of GPR55. In contrast, 17?-estradiol could increase the expression of GPR55 in ovarian cancer cell line SKOV-3. LPI-GPR55 and 17?-estradiol could induce ovarian cancer cell proliferation through a signalling pathway involving the activation of ERK1/2.